2015
DOI: 10.1371/journal.pone.0121911
|View full text |Cite
|
Sign up to set email alerts
|

Repositioning of Memantine as a Potential Novel Therapeutic Agent against Meningitic E. coli–Induced Pathogenicities through Disease-Associated Alpha7 Cholinergic Pathway and RNA Sequencing-Based Transcriptome Analysis of Host Inflammatory Responses

Abstract: Neonatal sepsis and meningitis (NSM) remains a leading cause worldwide of mortality and morbidity in newborn infants despite the availability of antibiotics over the last several decades. E. coli is the most common gram-negative pathogen causing NSM. Our previous studies show that α7 nicotinic receptor (α7 nAChR), an essential regulator of inflammation, plays a detrimental role in the host defense against NSM. Despite notable successes, there still exists an unmet need for new effective therapeutic approaches … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 54 publications
1
24
0
1
Order By: Relevance
“…It is also a transcriptional activator of many genes involved in the pathogenic triad of BM (e.g., IL–1β, TNF–α, IL-6, IL-8). During the past several decades, evidence has accumulated that deregulated activity of this pathway has been linked to the progression of a number of human diseases, including cancer, BM, rheumatoid arthritis, streptococcal cell wall-induced arthritis, experimental colitis, septic shock, Alzheimer's disease, multiple sclerosis, traumatic CNS injury, and cerebral ischemia (Koedel et al, 2000 ; de Souza et al, 2011 ; Anthony Jalin et al, 2015 ; Bennani-Baiti et al, 2015 ; Yu et al, 2015 ). Therefore, the NF-kB signaling pathway should be a good drug target that can hasten development of novel therapeutic agents.…”
Section: Nf-κb Signaling Pathway: the Mechanistic Link Of The Triad Amentioning
confidence: 99%
“…It is also a transcriptional activator of many genes involved in the pathogenic triad of BM (e.g., IL–1β, TNF–α, IL-6, IL-8). During the past several decades, evidence has accumulated that deregulated activity of this pathway has been linked to the progression of a number of human diseases, including cancer, BM, rheumatoid arthritis, streptococcal cell wall-induced arthritis, experimental colitis, septic shock, Alzheimer's disease, multiple sclerosis, traumatic CNS injury, and cerebral ischemia (Koedel et al, 2000 ; de Souza et al, 2011 ; Anthony Jalin et al, 2015 ; Bennani-Baiti et al, 2015 ; Yu et al, 2015 ). Therefore, the NF-kB signaling pathway should be a good drug target that can hasten development of novel therapeutic agents.…”
Section: Nf-κb Signaling Pathway: the Mechanistic Link Of The Triad Amentioning
confidence: 99%
“…Our laboratory has demonstrated that α7R is an essential regulator of the host inflammatory response against bacteria (Chi et al, 2011). α7R-mediated inflammatory effects could be blocked by its antagonist, MEM (Yu et al, 2015). Based on these findings, we hypothesized that MEM interacts first with the drug target α7R and then induce NET-mediated bacterial killing in PMNs.…”
Section: Introductionmentioning
confidence: 97%
“…These bacteria infect at least 2 million people per year in the USA alone, with 23,000 dying as a direct result of these infections (Khan and Siddiqui, 2014). It suggests that there is an emergent need to develop new antibacterial drugs with novel strategies (Yu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations